Joseph Beuys : Frühe Aquarelle - Schade, Werner (München : Schirmer/Mosel Verlag GmbH München, 1989)
The early watercolors of Joseph Beuys are numbered among the treasures of international public and especially, private collections. The viewer is struck by their aesthetic appeal - displaying the highest artistic sensitivity - as well as by the creative richness and conceptual and emotional depths that are revealed in these works. They show a profoundly contemplative and spiritual pictorial world from whose filigree structure Joseph Beuys drew essential correlations and concepts for his later work as a political artist. Drawing and painting watercolors helped him to gain a comprehensive awareness of his view of the world and man, and it also gave him the possibility of freely forming his colors from this liquid element. Created in the late forties and the fifties, these pictures are unparalleled in the art of the time and truly avant-garde. They established Joseph Beuys's reputation as one of the most important postwar artists, long before he entered the arena of public controversy with his revolutionary sculpture.
Literaturhinweise p. 107, Selected Bibliography p. 106
biog. p. 103-105, 103-105
Duits
boek
Keywords: Beuys, Joseph